Real-world software projects for computer science and engineering students - Gupta, Varun, 1987-; Nguyen-Duc, Anh (Software engineer) (Boca Raton, FL : CRC Press, 2021)
"Developing projects outside of a classroom setting can be intimidating for students and is not always a seamless process. Real-World Software Projects for Computer Science and Engineering Students is a quick, easy source for tackling such issues. Filling a critical gap in the research literature, the book: Is ideal for academic project supervisors. Helps researchers conduct interdisciplinary research. Guides computer science students on undertaking and implementing research-based projects This book explains how to develop highly complex, industry-specific projects, touching on real-world complexities of software developments. It shows how to develop projects for students who have not yet had the chance to gain real-world experience, providing opportunity to become familiar with the skills needed to implement projects using standard development methodologies. The book is also a great source for teachers of undergraduate students in software engineering and computer science as it can help students prepare for risk and uncertainty that is typical of software development in industrial settings"--
OCLC-licensed vendor bibliographic record.
Keywords: Computer programming -- Textbooks; Industrial engineering -- Data processing -- Textbooks; Project method in teaching; EDUCATION / Teaching Methods & Materials / Science & Technology